'Envacar - adverse reaction'. Issue 4 (18th February 1966) - Unknown
Abstract : Guanoxan (Envacar - Pfizer) is an antihypertensive drug which was introduced at the end of 1963; we published a preliminary assessment of it in 1964. 1 The drug is under trial in the United States, but has not yet been marketed there.